Manejo da adubação nitrogenada na cultura do milho pelo uso da inoculação com azospirillum brasilense em consórcio com capim xaraés - Souza, Wésley Carlos Rossini de [UNESP] (2014)
This study aimed to evaluate doses of nitrogen, with and without seed inoculation with bacteria Azospirillum brasilense cropped in spring/summer of 2011/12 and 2012/13 in single corn crop, and corn in autumn cropped in 2012 and 2013, intercropped with Urochloa brizantha cv. Xaraés. The experimental design for the four cropped was a randomized complete block design with four replications in a factorial 5 X 2, or five N topdressing (0, 30, 60, 90 and 120 kg ha -1 ) with and without the inoculation of corn seeds with A. brasilense at a dose of 100 mL per 25 kg of seed being intercropped by Urochloa brizantha cv. Xaraés the two autumnal cropped. Were evaluated at corn flowering, the levels of foliar nutrients and chlorophyll index, and crop yield components and grain yield of corn as well as the productivity of dry matter and crude protein content of the forage after the consortium. The topdressing, with N rates up to 120 kg ha -1 , increased linearly foliar nutrient levels and grain yield of irrigated corn grown in the spring/summer in the Cerrado soil, and crude protein of grass Xaraés in consortium with the autumnal corn. Inoculation of corn seeds with A. brasilense, in intercropping with Xaraés grass in autumnal time increased the nutrition, growth in plant height and yield components of corn, however, without effect on grain yield. Corn plants resulting from seeds inoculated with A. brasilense, by their greater vegetative growth, providing lower dry matter production of grass seed into Xaraés consortium with autumnal corn